Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Marlei, Pozzebon; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Keywords: Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Recherche; Technologie sociale; Transformations